The De Ritis ratio as prognostic biomarker of in‐hospital mortality in COVID‐19 patients. (25th October 2020) - Zinellu, Angelo; Arru, Francesco; De Vito, Andrea; Sassu, Alessandro; Valdes, Giovanni; Scano, Valentina; Zinellu, Elisabetta; Perra, Roberto; Madeddu, Giordano; Carru, Ciriaco; Pirina, Pietro; Mangoni, Arduino A.; et al.
Abstract: Increased concentrations of serum aspartate transaminase (AST) and alanine transaminase (ALT) are common in COVID‐19 patients. However, their capacity to predict mortality, particularly the AST/ALT ratio, commonly referred to as the De Ritis ratio, is unknown. We investigated the association between the De Ritis ratio on admission and in‐hospital mortality in 105 consecutive patients with coronavirus disease of 2019 (COVID‐19) admitted to three COVID‐19 referral centres in Sardinia, Italy. The De Ritis ratio was significantly lower in survivors than nonsurvivors (median: 1.25; IQR: 0.91‐1.64 vs 1.67; IQR: 1.38‐1.97, P  = .002) whilst there were no significant between‐group differences in ALT and AST concentrations. In ROC curve analysis, the AUC value of the De Ritis ratio was 0.701 (95% CI 0.603‐0.787, P  = .0006) with sensitivity and specificity of 74% and 70%, respectively. Kaplan‐Meier survival curves showed a significant association between the De Ritis ratio and mortality (logrank test P  = .014). By contrast, no associations were observed between the ALT and AST concentrations and mortality (logrank test P  = .83 and P  = .62, respectively). In multivariate Cox regression analysis, the HR in patients with De Ritis ratios ≥1.63 (upper tertile of this parameter) remained significant after adjusting for age, gender, smoking status, cardiovascular disease, intensity of care, diabetes, respiratory diseases, malignancies and kidney disease (HR: 2.46, 95% CI 1.05‐5.73, P  = .037). Therefore, the De Ritis ratio on admission was significantly associated with in‐hospital mortality in COVID‐19 patients. Larger studies are required to confirm the capacity of this parameter to independently predict mortality in this group.